Allelopathic property of an invasive tree Broussonetia papyrifera (L.) LHer. ex vent in its introduced range in mount Makiling forest reserve, Philippines - Combalicer, Marilyn S.; Carayugan, Mark Bryan A.; Hernandez, Jonathan O. (2019)
Invasive plants are responsible for many adverse ecological and economic impacts on forest ecosystems. These impacts and the emerging concern about protecting and conserving native species against invasive plants necessitate determining the invasive ability of all introduced plants in the country. In this study, the allelopathic property of stem and root of an invasive tree ? Broussonetia papyrifera ? was analyzed to give insights on important mechanisms underlying its invasive ability in its introduced range in Mount Makiling Forest Reserve (MMFR). Varying concentrations of aqueous extracts of stem and root of B. papyrifera were tested on a native tree, Sindora supa (test plant), to determine its effect on the morphological and physiological characteristics of the test plant. Results showed that the phytotoxicity of allelochemical(s) possibly contained within the aqueous root and stem extracts of B. papyrifera is extract-concentration-dependent. The stem and root extracts of B. papyrifera exhibited both inhibitory and stimulatory effects, which are typical of allelopathic plants. Therefore, one possible important mechanism of B. papyrifera underlying invasibility is its root and stem allelopathic property, posing a serious threat to native plants in the vicinity of MMFR. However, additional studies such as the identification of allelochemical compounds present in B. papyrifera and field trials are recommended. This is to better understand the inhibitory and stimulatory effects of B. papyrifera at the plant community level. (Author's abstract)